Perencanaan Perawatan dan Perbaikan Transmission Box Mesin Drilling Diameter Mata Bor Maksimum 20 mm - Ahmad Zulfikar; Syamsul Hadi; Marshel Oscar Himawan; Mus’ab Idzharul Huda; Rahmad Fardani; Wildan Raka Chipit (Jurnal Kendali Teknik dan Sains, 2026)
Problems in the transmission box of the Drilling Machine 438-02-814-0925 type (0.75 HP, 230/400V, 1425 rpm, produced in 1988) are the degradation of mechanical components for the pulley, V-belt, and rolling bearing. The purpose of maintenance and repair planning is to obtain maintenance costs, maintenance schedules in the period 2026, and the ratio of maintenance costs to profits. The maintenance and repair planning method includes collecting previous maintenance data; application of the inspection-replace-repair-overhaul (IRRO) method; evaluation of the working conditions of components, especially on the pulley, V-belt, spindle pulley (driven pulley), and rolling bearing; prediction of component service life; prediction of repairman costs; prediction of supporting equipment that will be used in maintenance; prediction of spare part replacement time or reinstallation of components after repair; estimation of maintenance and repair costs in 2026; and calculation of the ratio of maintenance costs to profits. The results of maintenance and repair planning obtained maintenance costs in 2026 amounting to Rp 4,627,000 with an estimated Drilling Machine rental rate of Rp 75,000/hour which has the opportunity to be rented for 400 hours/year, and a maintenance cost to profit ratio of 15.42% which implies that the Drilling Machine still has the opportunity to generate profits and is suitable for use in the coming years.